Communication Empowerment Framework: An integrative framework to support effective communication and interaction between carers and people living with dementia. (August 2020) - Morris, Lydia; Mansell, Warren; Williamson, Tracey; Wray, Alison; McEvoy, Phil
Objectives: To demonstrate the power of integrating three theoretical perspectives (Mentalization Theory, Perceptual Control Theory and the Communicative Impact model), which jointly illuminate the communication challenges and opportunities faced by family carers of people with dementia. To point the way to how this framework informs the design and delivery of carer communication and interaction training. Method: Conceptual synthesis based on a narrative review of relevant literature, supported by examples of family carers. Results: We use the conceptual models to show how the capacity to mentalize ("holding mind in mind") offers a greater sense of control over internal and external conflicts, with the result that they can be deescalated in pursuit of mutual goals. Conclusions: The integrative conceptual framework presented here highlights specific psychological and relational mechanisms that can be targeted through carer training to enhance communication with a person living with dementia.